Effectiveness of a multicomponent intervention on the screen time of Brazilian adolescents: non-randomized controlled study - Jéssika Aparecida Jesus Vieira; Luiz Rodrigo Augustemak de Lima; Diego Augusto Santos Silva; Edio Luiz Petroski (Universidade Estadual Paulista (UNESP), 2018)
Abstract Aim: The aim of this study was to verify the effectiveness of a multicomponent, school-based intervention in reducing screentime in adolescents according to sex. Methods: This is a non-randomized controlled intervention study focusing on cardiorespiratory fitness, body image, nutrition and physical activity. Screentime (television, computer/video game) was the secondary outcome of the intervention and was addressed using educational strategies (folders, posters, educational sessions and group discussions). Screen time was measured using a structured questionnaire validated in Brazilian adolescents and the excess time spent on-screen was defined as two hours or more daily. The effect of the intervention was analyzed by the McNemar test and logistic regression. Results: Intervention effectively reduced the proportion of adolescents exposed to more than two hours a day of computer/videogame in males from 71.7% to 57.5% (p= 0.002) and excessive time of television in females from 81.5% to 72.6% (p = 0.024), from the beginning to the end of the study in the group receiving intervention. However, no effect of intervention was found in the comparison between intervention and control groups for computer/video game time (OR = 0.822; p = 0.504) and television time (OR = 0.667; p = 0.252). Conclusion: The intervention was not effective in reducing screen time in the comparison between intervention and control groups, but it reduced the screen time of adolescents in the intervention group.